Proposta de metodologia para avaliação de acessibilidade em cidades de porte médio : um estudo de caso em São José do Rio Preto - Bernal, Luciana Mação (2016)
This research aims to propose a methodology for accessibility evaluation in middle-sized cities presenting a case study held in São José do Rio Preto (SP), city in the northwest of the São Paulo state. For this, the research used is based on a quality indicator (SQI – Sidewalks Quality Index, developed by Ferreira e Sanches, 2001). The questionnaires application in wheelchair users allowed the information collection in a qualitative and quantitative level regarding of security, comfort and environment in sidewalks and crossings and the carry through of a technical evaluation in the central area of the city. From these steps, as a methodology proposal, it was possible to elaborate an Accessibility Evaluation Index (AEI). This index was applied in the central area of the case study and an auditing (validation) was realized in order to verify the correct elaboration of the index. The present research was applied in a middle-sized city, the city type that has the fastest currently increase (IBGE, 2010), making the index an important accessibility evaluation tool. Thus, it grants the correction of identified accessibility problems avoiding the formation of cities whit segregated spaces, in people with some type of deficiency, with reduced mobility or elders do not have access to the city.